JURIDICAL REVIEW RECONSTRUCTION REGULATION OF COPYRIGHT AS A MATERIAL GUARANTEE - Handiriono, Raden; Gunawan, Sigit; Karina, Siska; Kamil, Insan (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The increasing economic role of Copyright as material security raises significant questions regarding how to qualify Copyright as material security and the ideal form of regulation of copyright use as material security. This research aims to conduct a juridical review of the use of Copyright as material security with a focus on the qualifications of Copyright as material security and the formulation of ideal arrangemecopyright use as material security research is qualitative research, namely using normative juridical methods by analyzing statutory regulations and the opinions of legal experts. This research found challenges in implementing Copyright as material collateral because there are no technical implementing regulations, such as enforcing rules for estimating intellectual property objects and financial services authority regulations so that banks and financial institutions can use Copyright as material collateral.